The Evidence for Fertility Preservation in Pediatric Klinefelter Syndrome - Pook, Celina J.; Cocca, Alessandra; Grandone, Anna; Al-Hussini, Mohamed; Lam, Wayne (Frontiers in Reproductive Health, 2021)
Klinefelter syndrome (KS) is a common cause of non-obstructive azoospermia (NOA). Advances in fertility preservation (FP) techniques, such as the use of microdissection testicular sperm extraction (micro-TESE), have improved sperm retrieval rates (SRR) up to 40–50% in this population. Age has been suggested to have an impact on FP, postulating that sperm production may deteriorate over time due to germ cell loss. As such, sperm retrieval for patients with KS at a younger age has been proposed to further improve SRR; however, whether such practice pragmatically improves SRR is yet to be determined, and controversy remains with concerns over trauma caused by FP procedures on further impairment of testicular function. There has also been a debate on the ethics of performing FP procedures in the pediatric population. Optimizing FP for patients with KS invariably requires a holistic multidisciplinary approach. This review aimed to evaluate the latest evidence in performing FP in pediatric patients with KS, and discuss the controversy surrounding such practice. Hormonal changes in patients with KS during childhood and the use of hormonal manipulation to optimize SSR in this population have also been reviewed.